Pengaruh Teknik Relaksasi Terhadap Penurunan Nyeri Epigastrium Pada Pasien Gastritis - Nuryanti, Erni; Abidin, M. Zainal; Normawati, Ajeng Titah (Jurnal Studi Keperawatan, 2020)
ABSTRACTBackground: Today the frequency of psychosomatic illnesses experienced by a person is increasing. One such psychosomatic disease is gastritis. Pharmacotherapy for gastritis often results in less satisfactory results. Meanwhile the other alternatives to overcome these problems can be done with relaxation exercises. Relaxation can increase the sensitivity of baro-reflect and decrease sympathetic nerve activity and activate the correction so that there will be a decrease of pain level.Objective: To know the effect of relaxation technique on the reduction of epigastria pain in gastritis patients.Research Method: The design of the research used is one group pre test and post test design, where the patient came to check the level of pain with the scale of pain then done relaxation. After the relaxation was done and then re-check in the same way. Bivariate analysis used Wilcoxon Test.Results: The statistical results obtained p = 0,000 (P 0.05) which means that there is a very significant difference in the average value of the pain scale before relaxation with the average of pain scale after relaxation.Conclusion: There is a relaxation effect on the reduction of epigastria pain in gastritis patients Keyword : Relaxation, Pain, Epigastria